Prevalence of hypertension and its associated factors among government employees in Doti district of Nepal - Ramesh Malashi; Sunita Sharma; Srijana Adhikari; Chitra Raj Sharma; Arun Kumar Joshi; Buna Bhandari (PLoS ONE, 2025)
Introduction Hypertension is a significant risk factor for cardiovascular diseases (CVDs), which remains the leading causes of morbidity and mortality globally, with a disproportionate impact on low and middle income countries. While hypertension is prevalent across various populations, government employees are particularly susceptible due to high stress levels, sedentary lifestyles, and work-related pressures. Therefore, this study was undertaken to assess the prevalence of hypertension and its associated risk factors among government employees in the Doti district of Nepal. Methods A cross-sectional study was carried out among 195 government employees in Dipayal Silgadhi Municipality of Doti district of Sudurpashchim province of Nepal. The data was collected through face-to-face interviews using Simple Random Sampling (SRS) technique and analysed using SPSS v25. The structured questionnaire adopted from the WHO STEPS survey tool was used for data collection. Bivariate and multivariate logistic regression model was used to assess the factors associated with hypertension. Results The prevalence of hypertension among government employee was 36.4%% ± 5.6%. Participants with age group 30–40 years [Adjusted Odd’s Ratio (AOR) 14.4, 95% Confidence Interval (CI) (1.6, 127.7)], 40–50 years [AOR 13.7, 95% CI (1.04, 180.3)] and work experience (20–30 years) [AOR 6.67, 95% CI(1.23, 35.9), and drinking alcohol [AOR 0.35, 95% CI (0.17, 0.72)] were found to be statistically significant with hypertension. Conclusion The study revealed the high prevalence of hypertension among government employees; significantly associated with risk factors like age group 30–50 years, work experience and alcohol consumption, indicating an alarming public health concern. These results highlight the pressing need for focused interventions to reduce the risk of hypertension and its related problems among government employees, such as lifestyle changes, workplace health programs, and routine health screenings.